Estimating the Tinnitus Spectrum: A Comparison Between At-Home and Laboratory Measurements. - Lentz, Jennifer J.; Yi Liu (American Journal of Audiology, 2025)
Purpose: The purpose of this study was to provide proof of concept for athome measurements of the tinnitus spectrum. Method: Nineteen participants completed pitch similarity ratings in the laboratory and at home. All participants first completed laboratory tests (at 500-16000 Hz) and then later completed at-home tests (at 250-8000 Hz) using their own personal computers and headphones. Six participants repeated these measurements after at least 3 weeks. Results: Tinnitus spectra (plots of pitch similarity rating vs. frequency) were analyzed using linear regression and Bland--Altman plots for frequencies that were common to both environments (500-8000 Hz). Although the Bland--Altman plots indicated that absolute ratings used by participants differed in the two settings with online ratings tending to be higher than lab ratings, the regression analysis indicated that the tinnitus spectra had similar shapes (evidenced by significantly positive slopes) between the two environments for 14 of the 19 participants. Similar results were evident for test--retest reliability of the six returning participants in both settings. Conclusions: We conclude that the pitch similarity rating method is potentially viable for measuring tinnitus pitch at home. At-home implementation could expedite clinical tinnitus assessments and could be used in conjunction with athome implementations of tinnitus treatment strategies. However, future studies should include participants who are tested at home prior to being tested in the lab and include an evaluation of extended high frequencies at home.